Determinants of Adoption of Improved Cassava Technologies among Farmers in Benue State, Nigeria - , Juliet Ogadinma Onyemma; , Nnaemeka Charles Onyemauwa; , Uwandu Queen Chioma; , Solomon Chimela Nwafor (Archives of Current Research International, 2020)
Aims: The study assessed the determinants of adoption of improved cassava technologies among farmers in Benue state, Nigeria Study Design: Survey design was used for the study. Place and Duration of Study: The study was carried out in Benue State, between February 2019 to November 2020. Methodology: the study comprised all farm families in Benue State. Cluster and simple random sampling techniques were used in the selection of 336 respondents for the study. Results: The result clearly showed that most of the respondents were in their active and productive age group, both male and female were involved in the production of cassava with the number of male slightly higher than female and that 90% of the farmers have had one form of formal education or another with mean farming experience of 14 years with limited access to extension services. There is high awareness of improved cassava technologies among farmers in Benue state but with moderate to low adoption of improved cassava technologies. The major factors that determined the adoption level in the area included characteristics of an innovation which are availability of inputs 100%, affordability 100%, storability 80.3%, quality of the processed products 81%, and acceptability of the products 95% (349). Others include farming experience 98%, adequate knowledge of the technology 83% (303), extension contact 86%, age 86%, income 85%, marital status 76% and gender 81%. Conclusion: The major factors that determine the adoption level in the area included characteristics of an innovation which are availability of inputs, affordability, quality of the processed products and acceptability of the products. Others include farming experience, adequate knowledge of the technology, extension contact. It was recommended that extension agents should ensure that improved cassava technologies are accessible by farmers and that farmers acquire the necessary knowledge and skills in using such technologies.